Correlation between Resistance of Pseudomonas aeruginosa to Quaternary Ammonium Compounds and Expression of Outer Membrane Protein OprR - Tabata, Atsushi (American Society for Microbiology, 2003)
The adaptation mechanism of Pseudomonas aeruginosa ATCC 10145 to quaternary ammonium compounds (QACs) was investigated. A P. aeruginosa strain with adapted resistance to QACs was developed by a standard broth dilution method. It was revealed that P. aeruginosa exhibited remarkable resistance to N-dodecylpyridinium iodide (P-12), whose structure is similar to that of a common disinfectant, cetylpyridinium chloride. Adapted resistance to benzalkonium chloride (BAC), which is commonly used as a disinfectant, was also observed in P. aeruginosa. Moreover, the P-12-resistant strain exhibited cross-resistance to BAC. Analysis of the outer membrane protein of the P-12-resistant strain by two-dimensional polyacrylamide gel electrophoresis showed a significant increase in the level of expression of a protein (named OprR) whose molecular mass was approximately 26 kDa. The actual function of OprR is not yet clear; however, OprR was expected to be an outer membrane-associated protein with homology to lipoproteins of other bacterial species, according to a search of the National Center for Biotechnology Information website with the BLAST program by use of the N-terminal sequence of OprR. A correlation between the level of expression of OprR and the level of resistance of P. aeruginosa to QACs was observed by using a PA2800 gene knockout mutant derived from the P-12-resistant strain. The knockout mutant recovered susceptibility not only to P-12 but also to BAC. These results suggested that OprR significantly participated in the adaptation of P. aeruginosa to QACs, such as P-12 and BAC.